PENGARUH BEBAN KERJA TERHADAP TURNOVER INTENTION PADA MAHASISWA MANAJEMEN ANGKATAN 2022 YANG BEKERJA SAMBIL KULIAH - Vika Fajariyani; Puji Isyanto (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research aims to analyze the impact of workload on turnover intention among students of the Management Study Program at Universitas Buana Perjuangan Karawang class of 2022 who work while attending lectures. Students may experience physical and psychological pressure due to managing their tasks as workers and learners, which can ultimately affect their desire to change jobs. This study uses a causal strategy along with a quantitative approach. Purposive sampling is used to select a sample from thirty respondents. A Likert scale questionnaire is used to collect data, and SPSS software is used for basic linear regression analysis. With a regression coefficient of 0.350 and a significance value of 0.040 (< 0.05), the findings indicate that workload has a positive and significant impact on turnover intention. Therefore, students are more likely to intend to change jobs if they feel a heavier workload.